Nalmefene attenuates neural alcohol cue-reactivity in the ventral striatum and subjective alcohol craving in patients with alcohol use disorder - Karl, Damian; Bumb, Jan Malte; Bach, Patrick; Dinter, Christina; Koopmann, Anne; Hermann, Derik; Mann, Karl; Kiefer, Falk; Vollstädt-Klein, Sabine (Psychopharmacology, 2021)
Alcohol use disorder is a common and devastating mental illness for which satisfactory treatments are still lacking. Nalmefene, as an opioid receptor modulator, could pharmacologically support the reduction of drinking by reducing the (anticipated) rewarding effects of alcohol and expanding the range of treatment options. It has been hypothesized that nalmefene acts via an indirect modulation of the mesolimbic reward system. So far, only a few imaging findings on the neuronal response to nalmefene are available.
Gesehen am 04.01.2023